SPAD index, nitrates, and sorghum yield in response to nitrogen supply - Macías-Duarte, Rubén (2021)
Introduction. Nitrogen (N) is the macronutrient that most affects crop yield, however, the utilization by crops is associated with a low recovery efficiency; for this reason, it is necessary to analyze its absorption into the plant tissue during the cycle to obtain the desired benefit. Objective. To know the effect of nitrogen fertilization on growth, nitrate concentration at the base of the stem (NBT), SPAD index (chlorophyll), and yield of sorghum (Sorghum bicolor L. Moench) grain. Materials and methods. The study was conducted at the Instituto de Ciencias Agrícolas of the Universidad Autónoma de Baja California, Mexico, during the summer 2012, and spring 2013. Increasing doses of nitrogen (N) (0, 64, 128, 192, 256, and 320 kg ha-1) were evaluated using a randomized experimental design. On Experiment 1 (Summer 2012), six nitrogen rates were evaluated in a soil under conservation tillage (LC). On Experiment 2 (Spring 2013) the same doses of nitrogen were evaluated and a treatment of 128 kg ha-1 was also included using the minimum tillage system (LM). Results. On Experiment 1, a greater amount of grain dry weight (PSg), complete plant (PSt), harvest index (IC), and grain yield was obtained than in Experiment 2. Major PSg, PSt, IC, foliar area (AF), and yield grain was obtained with the dose of 192 kg de N ha-1. The SPAD index, and the nitrate concentration on NBT were correlated with yield. Values of R2 on the SPAD index were higher than those found on NBT. Conclusions. The NBT and SPAD index were significantly associated with yield. The best season for sorghum grain production was summer with 192 kg N ha-1.